Probiotic supplementation attenuates age‐related sarcopenia via the gut–muscle axis in SAMP8 mice. Issue 1 (11th November 2021) - Chen, Li‐Han; Chang, Shy‐Shin; Chang, Hsin‐Yi; Wu, Chieh‐Hsi; Pan, Chun‐Hsu; Chang, Chun‐Chao; Chan, Ching‐Hung; Huang, Hui‐Yu
Abstract: Background: Age‐related muscle dysfunctions are common disorders resulting in poor quality of life in the elderly. Probiotic supplementation is a potential strategy for preventing age‐related sarcopenia as evidence suggests that probiotics can enhance muscle function via the gut–muscle axis. However, the effects and mechanisms of probiotics in age‐related sarcopenia are currently unknown. In this study, we examined the effects of Lactobacillus casei Shirota (LcS), a probiotic previously reported to improve muscle function in young adult mice. Methods: We administered LcS (1 × 10 8 or 1 × 10 9 CFU/mouse/day) by oral gavage to senescence‐accelerated mouse prone‐8 mice for 12 weeks (16‐ to 28‐week‐old). Sixteen‐week‐old and 28‐week‐old SMAP8 mice were included as non‐aged and aged controls, respectively. Muscle condition was evaluated using dual‐energy X‐ray absorptiometry for muscle mass, holding impulse and grip strength tests for muscle strength, and oxygen consumption rate, gene expressions of mitochondrial biogenesis, and mitochondrial number assays for mitochondria function. Inflammatory cytokines were determined using enzyme‐linked immunosorbent assay. Gas chromatography–mass spectrometry was utilized to measure the short‐chain fatty acid levels. The gut microbiota was analysed based on the data of 16S rRNA gene sequencing of mouse stool. Results: The LcS supplementation reduced age‐related declines in muscle mass (>94.6%, P < 0.04), strength (>66% in holding impulse and >96.3% in grip strength, P < 0.05), and mitochondrial function ( P < 0.05). The concentration of short‐chain fatty acids (acetic, isobutyric, butyric, penic, and hexanoic acid) was recovered by LcS (>65.9% in the mice given high dose of LcS, P < 0.05) in the aged mice, and LcS attenuated age‐related increases in inflammation ( P < 0.05) and reactive oxygen species (>89.4%, P < 0.001). The high dose of LcS supplementation was also associated with distinct microbiota composition as indicated by the separation of groups in the beta‐diversity analysis ( P = 0.027). LcS supplementation altered predicted bacterial functions based on the gut microbiota. Apoptosis ( P = 0.026), p53 signalling ( P = 0.017), and non‐homologous end‐joining ( P = 0.031) were significantly reduced, whereas DNA repair and recombination proteins ( P = 0.043), RNA polymerase ( P = 0.008), and aminoacyl‐tRNA biosynthesis ( P = 0.003) were increased. Finally, the genera enriched by high‐dose LcS [linear discriminant analysis (LDA) score > 2.0] were positively correlated with healthy muscle and physiological condition ( P < 0.05), while the genera enriched in aged control mice (LDA score > 2.0) were negatively associated with healthy muscle and physiological condition ( P < 0.05). Conclusions: Lactobacillus casei Shirota represents an active modulator that regulates the onset and progression of age‐related muscle impairment potentially via the gut–muscle axis.